Mentalization-oriented psychodynamic group therapy for patients with personality disorders: a naturalistic prospective cohort study. (1st February 2023) - Svensson, Bo Anton; Bredtoft, Jacob; Stenager, Elsebeth; Larsen, Pia Veldt; Skøt, Lotte; Sibbersen, Christian; Mellentin, Angelina Isabella
Abstract: Objectives: Patients with personality disorders (PDs) are often treated with non-manualized psychodynamic group therapy (PDT) lasting for several years. Non-manualized PDT often combines a variety of therapeutic approaches from different PDT traditions, including mentalization-based therapy. Currently, little is known about the effect of this long-term, costly treatment. This study investigated the extent to which patients with different PDs benefit from mentalization-oriented PDT as it is implemented in clinical practice in terms of symptom severity, interpersonal problems, and general functioning. Methods: The design was a naturalistic, prospective cohort study. Seventy-five consecutive PD patients were assessed before treatment with the Symptom Checklist-90 Revised (SCL-90-R) as the primary outcome measure and the Inventory of Interpersonal Problems (IIP) and Global Assessment of Functioning (GAF) as secondary outcome measures. The sample was repeatedly assessed every 12 months for up to 36 months. Paired t -tests were applied to examine the effectiveness of the intervention. Results: Among completers ( n  = 42; 56%), improvement was observed on the SCL-90-R: Global Severity Index (mean change = −0.45 [95% CI = –0.72, −0.19]; Cohen's d  = –0.55), Positive Symptom Distress Index (–0.40 [–0.63, −0.17]; −0.56); Positive Symptoms Total (–10.70 [–17.31, −4.09]; −0.52). Secondary outcomes also improved: IIP-total (mean change = –0.50 [95%CI = –0.74, −0.25]; Cohen's d  = –0.66); GAF-Functioning (8.79 [6.32, 11.27]; 1.15); and GAF-Symptoms (10.67 [8.09, 13.25]; 1.34). Conclusions: Completers improved on symptom severity, interpersonal problems, and general functioning, with within-group effect sizes ranging from medium to large. Approximately half the sample dropped out, suggesting that mentalization-oriented PDT spanning several years may be unrealistic for many patients with PD. Significant outcomes: There are no clear guidelines for psychological interventions targeting personality disorders (PDs), and currently eclectic and non-manualized psychodynamic approaches lasting for up to 3 years are prevailing in some clinical practices. Although this treatment approach may have an effect on compliant patients, the high drop-out rate indicates that it may not be suitable for a large proportion of PD patients since it requires long-term commitment. Furthermore, it is difficult to identify the content of the non-manualized psychodynamic therapy and what helps the patients. More specific clinical guidelines emphasizing the application of evidence-based treatments or at least manualized treatments are warranted for the treatment of emotionally unstable PDs and other PDs. Limitations: The naturalistic study design, without any control group, limits conclusions about mechanisms of action of the intervention. Since the intervention was not manualized, it is unknown exactly which treatment was actually administered, which reduces external validity. The outcomes are based on completer data of a relatively small sample size with high drop-out rate.